Measurement of physician-patient communication--a systematic review. - Jördis M Zill; Eva Christalle; Evamaria Müller; Martin Härter; Jörg Dirmaier; Isabelle Scholl (PLoS ONE)
Background Effective communication with health care providers has been found as relevant for physical and psychological health outcomes as well as the patients' adherence. However, the validity of the findings depends on the quality of the applied measures. This study aimed to provide an overview of measures of physician-patient communication and to evaluate the methodological quality of psychometric studies and the quality of psychometric properties of the identified measures. Methods A systematic review was performed to identify psychometrically tested instruments which measure physician-patient communication. The search strategy included three databases (EMBASE, PsycINFO, PubMed), reference and citation tracking and personal knowledge. Studies that report the psychometric properties of physician-patient communication measures were included. Two independent raters assessed the methodological quality of the selected studies with the COSMIN (COnsensus based Standards for the selection of health status Measurement INtruments) checklist. The quality of psychometric properties was evaluated with the quality criteria of Terwee and colleagues. Results Data of 25 studies on 20 measures of physician-patient communication were extracted, mainly from primary care samples in Europe and the USA. Included studies reported a median of 3 out of the nine COSMIN criteria. Scores for internal consistency and content validity were mainly fair or poor. Reliability and structural validity were rated mainly of fair quality. Hypothesis testing scored mostly poor. The quality of psychometric properties of measures evaluated with Terwee et al.'s criteria was rated mainly intermediate or positive. Discussion This systematic review identified a number of measures of physician-patient communication. However, further psychometric evaluation of the measures is strongly recommended. The application of quality criteria like the COSMIN checklist could improve the methodological quality of psychometric property studies as well as the comparability of the studies' results.